2013
DOI: 10.1007/s13580-013-0166-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physicochemical characteristics during fruit development in June-bearing strawberry cultivars

Abstract: Abstract. Changes in physicochemical characteristics were investigated during fruit development in 'Maehyang', 'Seolhyang', 'Keumhyang', 'Akihime', and 'Red Pearl' strawberries. Fresh weights and color parameters of strawberry fruits changed significantly during the fruit development in all cultivars. Fruit shapes of 'Maehyang' and 'Akihime' were conical, with an index of length to width being 1.5 and that of 'Seolhyang', 'Keumhyang', and 'Red Pearl' were cordate, the index being 1.3. Firmness decreased as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 31 publications
3
20
0
1
Order By: Relevance
“…Zhang et al (2013) also detected higher content levels of anthocyanins in mature fruit than in immature fruits due to significant increase in the expression of genes related to anthocyanin biosynthesis. Similar to our results, previous studies reported that anthocyanin concentration increased during fruit maturation (Kim et al, 2013). Sugars are the initial precursors in anthocyanin biosynthesis, and there is a direct relationship between sugar content and total anthocyanins in grape (Gonzalez-SanJose & Diez, 1992) and apples (Bizjak, Weber, et al, 2013).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Zhang et al (2013) also detected higher content levels of anthocyanins in mature fruit than in immature fruits due to significant increase in the expression of genes related to anthocyanin biosynthesis. Similar to our results, previous studies reported that anthocyanin concentration increased during fruit maturation (Kim et al, 2013). Sugars are the initial precursors in anthocyanin biosynthesis, and there is a direct relationship between sugar content and total anthocyanins in grape (Gonzalez-SanJose & Diez, 1992) and apples (Bizjak, Weber, et al, 2013).…”
supporting
confidence: 91%
“…Total ellagic acid content in grape skin averagely increased 1.7-fold during ripening (Lee & Talcott, 2004). Contrary, ellagic acid content decreased in strawberry fruit as the fruit matured (Kim et al, 2013).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Kim et al [23] reported the anthocyanins content of strawberry cultivars at red stage ranged from 38.3-60.8mg/100g of fw. Pelayo et al [24] reported that distribution of anthocyanins pigment in fruit tissues of different strawberry cultivars is not uniform.…”
Section: Discussionmentioning
confidence: 99%
“…During their shelf life, strawberries are generally qualified based on their colour, firmness, calyx decay and fruit decay (Collins and Perkins-Veazie, 1993;Nunes et al, 1995;Villarreal et al, 2008). However, they are also qualified on their aroma and taste (Pelayo et al, 2003;Kim et al, 2013). Ripe strawberry fruits produce hundreds of different aroma volatiles, culminating into a complex aroma that is cultivar specific (Ulrich et al, 1997;Forney et al, 2000;Schwieterman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%